2014
DOI: 10.1186/1471-2318-14-71
|View full text |Cite
|
Sign up to set email alerts
|

Risk of death or hospital admission among community-dwelling older adults living with dementia in Australia

Abstract: BackgroundOlder people living with dementia prefer to stay at home to receive support. But they are at high risk of death and/or hospital admissions. This study primarily aimed to determine risk factors for time to death or hospital admission (combined) in a sample of community-dwelling older people living with dementia in Australia. As a secondary study purpose, risk factors for time to death were also examined.MethodsThis study used the data of a previous project which had been implemented during September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…These studies have reported that the venue of treatment does not affect the mortality rate, but that deterioration of motor and cognitive functions is less likely to occur when patients receive home care. [6][7][8][9] However, caution must be exercised when applying overseas-sourced findings directly to the Japanese context, as Japan has many unique aspects, including medical care and longterm care systems, culture and customs. We previously conducted a preliminary study of older people in Japan who regularly received home care; our findings suggested that when such individuals develop a fever, home care leads to a more favorable outcome than hospitalized care.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have reported that the venue of treatment does not affect the mortality rate, but that deterioration of motor and cognitive functions is less likely to occur when patients receive home care. [6][7][8][9] However, caution must be exercised when applying overseas-sourced findings directly to the Japanese context, as Japan has many unique aspects, including medical care and longterm care systems, culture and customs. We previously conducted a preliminary study of older people in Japan who regularly received home care; our findings suggested that when such individuals develop a fever, home care leads to a more favorable outcome than hospitalized care.…”
Section: Introductionmentioning
confidence: 99%
“…A study of community‐dwelling older adults with dementia found that a previous hospital admission or previously worse cognition increased the risk of hospital admission or death. Use of community services was considered a short‐term protective factor (You et al, ). The progressive nature of dementia and the long duration of dependency may limit the possibility of remaining at home until the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Use of community services was considered a short-term protective factor (You et al, 2014). The progressive nature of dementia and the long duration of dependency may limit the possibility of remaining at home until the end of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebrovascular and cardiovascular events, aspiration pneumonia, pressure ulcers, and delirium are the most frequent causes of death in individuals with dementia. [6][7][8] Additional information regarding the existence of specific cause of death at the end of the study could have been useful to understand the underlying mechanism. Finally, there are many types and three stages of dementia for which there are different mortality rates.…”
Section: Comments / Replies Defining Randomly Measured Glycemic Valuementioning
confidence: 99%